2015
DOI: 10.2466/10.25.pms.121c14x0
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Movement Skills of Preschool Children in Northwest England

Abstract: This cross-sectional study examined fundamental movement skill competency among deprived preschool children in Northwest England and explored sex differences. A total of 168 preschool children (ages 3–5 yr.) were included in the study. Twelve skills were assessed using the Children's Activity and Movement in Preschool Motor Skills Protocol and video analysis. Sex differences were explored at the subtest, skill, and component levels. Overall competence was found to be low among both sexes, although it was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
78
3
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 44 publications
15
78
3
7
Order By: Relevance
“…In terms of gender differentiation, 81.6% of girls scored at or below the 50 th percentile, in comparison to 64% of boys. Generally, these results reflect recent findings about the low level of FMS proficiency in preschool children (Foulkes et al, 2015;Hardy et al, 2009;LeGear et al, 2012). The poor level of FMS proficiency found in our study becomes more important because some studies have found that higher FMS proficiency in childhood results in a higher level of physical activity during adolescence (Barnett et al, 2009;Barnett, van Beurden, Morgan, Brooks, & Beard, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of gender differentiation, 81.6% of girls scored at or below the 50 th percentile, in comparison to 64% of boys. Generally, these results reflect recent findings about the low level of FMS proficiency in preschool children (Foulkes et al, 2015;Hardy et al, 2009;LeGear et al, 2012). The poor level of FMS proficiency found in our study becomes more important because some studies have found that higher FMS proficiency in childhood results in a higher level of physical activity during adolescence (Barnett et al, 2009;Barnett, van Beurden, Morgan, Brooks, & Beard, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Temple, Crane, Brown, Williams, and Bell (2016) suggested that young boys and girls may already have different physical activity preferences, which perhaps lead to differences in motor skills proficiency. Although there are often no differences, by gender, in terms of total FMS test scores, boys and girls often have different levels of specific subtest scores in locomotor, object control and balance skills (see Foulkes et al, 2015;Hardy et al, 2009;Kokštejn, Musálek, & Tufano, 2017). Generally, better object control skills have been found in boys (Foulkes et al, 2015;Hardy et al, 2009;Kokštejn et al, 2017;Livesey, Coleman, & Piek, 2007;Spessatto, Gabbard, Valentini, & Rudisill, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Object control skills are those that involve manipulation of an object, for example throwing, catching and kicking (Barnett et al, 2008a). Locomotor and object control skills are considered to be fundamental for future movement and engagement in later-life physical activity (Foulkes et al, 2013). Numerous studies have found relationships between motor development, fundamental movement proficiency and physical activity behaviors (Barnett et al, 2008a;Barnett et al, 2009;Barnett et al, 2008b;Okely et al, 2001;Piek et al, 2006;Ridgway et al, 2009).…”
Section: Typical Developmentmentioning
confidence: 99%
“…Some authors note that the basic motor movements develop from the second year until the seventh years of age [9,10]. However, the specific motor abilities are acquired in the seventh through the eleventh years of life [11].…”
Section: Introductionmentioning
confidence: 99%